Augmented reality-integrated digital worksheets in science education: research trends, educational outcomes, and future directions from a systematic literature reviews - Sri Wahyuni Sitorus; Sri Ngabekti; Sudarmin Sudarmin; Novi Ratna Dewi (Indonesian Institute For Counseling, Education and Therapy, 2026)
The demands of digital transformation in the 21st century require continuous innovation in the design of science teaching materials, especially to replace static printed instruments. The integration digital worksheets presented in flipbook format with Augmented Reality (AR) technology offers strategic potential in visualizing abstract concepts of Natural Sciences (IPA) into immersive and interactive three-dimensional representations. This Systematic Literature Review (SLR) research aims to map research trends, evaluate the level of validity and practicality of media, and identify research gaps related to the use of these technologies. This review was limited to 15 peer-reviewed primary articles indexed in academic databases in the 2020 to 2026 publication range. The results of the analysis show that all AR-visualized digital worksheet developed achieve a very valid and practical predicate. Empirically, this fusion of technology has proven to be effective in reducing cognitive burden, shifting the learning paradigm to student-centered, and significantly spurring student motivation and learning outcomes. However, the findings reveal that the current research focus is still concentrated at the high school level for abstract materials (Biology and Chemistry) and has not targeted the integration of Higher Order Thinking Skills (HOTS) assessments in depth. This SLR concludes that the future development of digital worksheets-AR must go beyond the feasibility of basic media by adopting high-level reasoning instruments and expanding the scale of testing to the higher education level.